Endovascular stent graft repair of complete persistent sciatic artery aneurysm with lower limb ischemia: A case report and review of the literature. (April 2019) - Wang, Yuewei; Xin, Hai; Tan, Haofei; Wang, Haofu
Background: Persistent sciatic artery is a rare embryological vascular anomaly, with an incidence of 0.01%–0.05%. Up to 60% of persistent sciatic artery patients will develop aneurysms that can subsequently lead to distal embolization and a high risk of limb loss. Method: Here we report a case with acute limb ischemia caused by thrombus in a right persistent sciatic artery aneurysm. The patient underwent endovascular treatment by deploying a 10 × 150 mm stent graft (Viabahn) in the persistent sciatic artery and two self-expanding bare stents (10 × 40 mm, 10 × 60 mm, SMART) in the stent graft to reinforce the radial resistive force. In addition, we conducted a literature review of articles published in PubMed from 2001 to 2018 regarding stent graft repair of complete persistent sciatic artery aneurysms. A total of 13 articles reported 13 patients with complete persistent sciatic artery aneurysms who underwent endovascular stent graft repair. Result: A favorable result was obtained for this patient, and computed tomographic angiography at 6 months of follow-up revealed patent stent graft. Most articles reported favorable results. Conclusion: Favorable results can be achieved with endovascular stent graft repair and anticoagulation therapy for complete persistent sciatic artery aneurysms.